Divulging two decades of multimedia applications in biology education - Abdullah, Khairul Hafezad (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
Biology is an indispensable component of Science, Technology, Engineering, and Mathematics (STEM) education. Accordingly, effective biology teaching necessitates multimedia to assist students in fathoming complex scientific themes. This study aims to scrutinise the bibliometrics of preceding publications on multimedia applications in biology education from the Scopus and Web of Science databases. This study explores descriptive publishing patterns and the emergence of academic discourse about multimedia applications in biology education using ScientoPy and VOSviewer. The results reveal publications on this topic have been volatile, with less than ten publications in both databases. The United States has bested others as the most noteworthy multimedia applications in biology education publication hubs. The top three keywords yielded by ScientoPy were